Applied polymer rheology polymeric fluids with industrial applications - Kontopoulou, Marianna (Wiley, 2012)
"Bridging the gap between theory and practice/application, the book explores state-of-the-art polymer rheology to help readers understand the relationship between molecular structure and the flow behavior of polymers. Functioning as a reference on the literature and technical approaches to polymer rheology, it places a focus on common industrially-used polymer systems. The book provides a comprehensive overview of the rheological characteristics of polymeric fluids of interest to industry so that plastics and polymer engineers, chemical engineers, materials scientists, polymer chemists, and physicists can interpret findings and plan experiments"--